THE IMPACT OF NURSING CARE PRACTICES ON TEACHING WORK - Espírito Santo Neto, Adelmo Fernandes do; Mantovani, Maria de Fátima; Khalaf, Daiana Kloh; Santana, Vanessa Piccinin Paz (Cogitare Enfermagem, 2024)
Objective: To understand the impact of nursing care practices on the efficacy of teaching work. Method: A qualitative, descriptive, and exploratory study with 12 professors working in undergraduate and technical nursing courses at a public teaching institution in southern Brazil. Data was collected from June to December 2022 using the focus group technique and individual interviews. Bardin's Thematic Content Analysis was used to process the data using Atlas.ti software. Results: Two categories emerged: professional experience in care and care as part of teaching. Final considerations: The study highlights the relevance of care practice in nursing teacher training and warns of the risks of transferring care to the classroom to preserve the teacher's work process and the training of professionals in the area.